Targeting diseased tissues by pHLIP insertion at low cell surface pH - Andreev, Oleg A.; Engelman, Donald M.; Reshetnyak, Yana K. (Frontiers in Physiology, 2014)
The discovery of the pH Low Insertion Peptides (pHLIPs) provides an opportunity to develop imaging and drug delivery agents targeting extracellular acidity. Extracellular acidity is associated with many pathological states, such as those in cancer, ischemic stroke, neurotrauma, infection, lacerations and others. The metabolism of cells in injured or diseased tissues often results in the acidification of the extracellular environment, so acidosis might be useful as a general marker for the imaging and treatment of diseased states if an effective targeting method can be developed. The molecular mechanism of a pHLIP peptide is based on pH-dependent membrane-associated folding. pHLIPs, being moderately hydrophobic peptides, have high affinities for cellular membranes at normal pH, but fold and insert across membranes at low pH, allowing them to sense pH at the surfaces of cells in diseased tissues, where it is the lowest. Here we discuss the main principles of pHLIP interactions with membrane lipid bilayers at neutral and low pHs, the possibility of tuning the folding and insertion pH by peptide sequence variation, and potential applications of pHLIPs for imaging, therapy and image-guided interventions.